Comparation of Phenotypic and Genotypic Profile of Carbapenemase Producing Escherichia coli - Sutandhio, Silvia; Budiono, Budiono; Hardiono, Hardiono; Kuntaman, Kuntaman; Wasito, Eddy Bagus; Lusida, Maria Inge (Folia Medica Indonesiana, 2018)
Carbapenemase-producing Escherichia coli (E. coli) has caused trouble in therapeutic antibiotic selection. Carbapenemase screening procedure in laboratories is usually based on inacurate semi-automatic system. Confirmation and classification of carbapenemases according to Ambler can be done with combination of phenotypic methods, i.e., Modified Hodge Test (MHT), Sodium Mercaptoacetic Acid (SMA), and 3-Aminophenylboronic Acid (PBA). This study aimed to compare profiles of carbapenemase-producing E. coli which were confirmed and classified phenotypically with the genotypic profiles. E. coli isolates from urine specimens which were potential as carbapenemase-producers according to semi-automatic system BD Phoenix were phenotypically tested with MHT, SMA, and PBA. Isolates were grouped as carbapenemase-producers and non carbapenemase-producers. Phenotypic carbapenemase-producer isolates were classified based on Ambler criteria. All isolates were then tested with Polymerase Chain Reaction (PCR) for the presence of OXA-48, IMP1, IMP2, GES, VIM, NDM, KPC genes. Out of 30 isolates, 6 isolates (20.0%) were MHT positive, and 25 isolates (83.3%) were SMA positive, which indicated that most isolates produced were carbapenemase Ambler B. PCR confirmed 12 isolates (40.0%) had VIM gene which were classified as carbapenemase Ambler B. Phenotypic confirmatory test had 100% sensitivity and 22.2% specificity. Classification with phenotypic confirmatory test had 91.7% match with PCR. Phenotypic confirmatory test detected more carbapenemase than PCR. This low specificity may be caused by inappropriate use of diagnostic gold standard. PCR should not be used for routine carbapenemase confirmation because of vast diversity of carbapenemases. Phenotypic confirmatory test can classify carbapenemase according to Ambler classification.